Harnessing Conductive Oxide Interfaces for Resistive Random-Access Memories - Li, Yang; Kvatinsky, Shahar; Kornblum, Lior (Frontiers in Physics, 2021)
Two-dimensional electron gases (2DEGs) can be formed at some oxide interfaces, providing a fertile ground for creating extraordinary physical properties. These properties can be exploited in various novel electronic devices such as transistors, gas sensors, and spintronic devices. Recently several works have demonstrated the application of 2DEGs for resistive random-access memories (RRAMs). We briefly review the basics of oxide 2DEGs, emphasizing scalability and maturity and describing a recent trend of progression from epitaxial oxide interfaces (such as LaAlO3/SrTiO3) to simple and highly scalable amorphous-polycrystalline systems (e.g., Al2O3/TiO2). We critically describe and compare recent RRAM devices based on these systems and highlight the possible advantages and potential of 2DEGs systems for RRAM applications. We consider the immediate challenges to revolve around scaling from one device to large arrays, where further progress with series resistance reduction and fabrication techniques needs to be made. We conclude by laying out some of the opportunities presented by 2DEGs based RRAM, including increased tunability and design flexibility, which could, in turn, provide advantages for multi-level capabilities.